Pictographic Representations of the Word “Nature” in Preschool Education Children - Fraijo-Sing, Blanca Silvia; Beltrán Sierra, Norma Isabel; Tapia-Fonllem, César; Valenzuela Peñúñuri, Rosalba (Frontiers in Psychology, 2020)
The relevance of preschool children’s understanding of nature, its elements, how it affects the behavior of human beings, and how human beings influence it, is a two-purpose task. First, it helps to identify the necessary elements for the design of programs that have a significant impact in the development of environmental identity. Second, it also assists in the implementation of environmental education in the school curriculum in Mexico, in order to develop attitudes to preserve the environment from an early age. Based on this logic, the objective of this study was to identify the components of the concept of nature and its relationship with environmental identity, from drawings made by preschool children in a desert environment through a visual discursive analysis. The sample consisted of 118 preschool students whose ages ranged between 5 and 6 years. Participants were selected from four different schools in Hermosillo, Mexico: three located in the urban area and one on the coastal area of the State of Sonora. Participants were asked to draw the first thing that came to their minds when they heard the word nature. As a result, all the drawings presented categories such as plants, animals, waterbodies, celestial bodies, abiotic factors, natural locations, locations made by man, and others. Finally, the analysis showed that a general idea of what nature represents to children includes elements of known flora and fauna; however, they did not capture elements of the desert region in which they live. In addition, most participants’ self-definition contained environmental identity.